Gambaran Pengetahuan, Sosiodemografi dan Budaya Orang Rimba Terkait Dengan Praktek Pencegahan COVID-19 (Berita Kedokteran Masyarakat (BKM), 2020)
AbstractCOVID-19 is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (Sars-CoV-2) virus. The World Health Organization has announced that COVID-19 is a pandemic disease. Orang Rimba is one of the indigenous groups in Jambi that still practice traditional ways of life. The purpose of this research is to describe knowledge, Sociodemographic, and cultural Of Orang Rimba Tribe related to COVID-19 prevention practices. Method:  This research is a descriptive study with cross sectional design. This research was held in Pamenang Sub-district of Merangin Regency, Jambi Province on April 27- June 6, 2020. As respondents in this study were all head of the Orang Rimba family at Pamenang sub-district, amounting to 62 respondents. The research instrument used in this study was a questionnaire. This research is a descriptive study with cross sectional design. The results showed knowledge of COVID-19 disease respondents low (93.5%), the age of the respondents mostly between 20-40 years (48.4%), the majority sex of respondents are male (82.3%), main majority occupation of respondents are hunter (43.5%), the majority of respondents staying on permanent houses (62.9%), the majority of respondents lived permanently (66.1%). Some respondents (33.9%) still having nomadic life style caused by social conflict (24.2%) and foraging (11.3%), most respondents did not practice COVID-19 prevention (82.3%) correctly. Conclusion: The knowledge of the Orang Rimba at Pamenang sub-district about COVID-19 is still low, the main occupation of the Orang Rimba are hunter, the majority of the Orang Rimba at Pamenang sub district have a house permanently and they stayed at home, Orang Rimba's at Pamenang sub district still practice a nomadic culture caused by conflict social and foraging activities, most of the Orang Rimba's at Pamenang sub-district didnot practice properly of the COVID-19 prevention. Keywords: COVID-19; knowledge; Sociodemography ; Orang Rimba culture